2018
DOI: 10.3390/genes9100464
|View full text |Cite
|
Sign up to set email alerts
|

B Chromosomes of the Asian Seabass (Lates calcarifer) Contribute to Genome Variations at the Level of Individuals and Populations

Abstract: The Asian seabass (Lates calcarifer) is a bony fish from the Latidae family, which is widely distributed in the tropical Indo-West Pacific region. The karyotype of the Asian seabass contains 24 pairs of A chromosomes and a variable number of AT- and GC-rich B chromosomes (Bchrs or Bs). Dot-like shaped and nucleolus-associated AT-rich Bs were microdissected and sequenced earlier. Here we analyzed DNA fragments from Bs to determine their repeat and gene contents using the Asian seabass genome as a reference. Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…Apart from the presence of transposons and pseudogenes/fragments of genes on Bs, the latest research studies [25,44,56,75,77,78,79] have also found protein coding intact genes that we call “B essential genes” (see definitions in Box 1) which might be critical for the survival and transmission of Bs during their earlier stages of evolution (see details in next topic section). To create a reference of B-linked genes, we have organized a database that contain a list of genes detected in different species (Supplementary Dataset S1).…”
Section: Genome Composition Origin and Evolution Of Bsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the presence of transposons and pseudogenes/fragments of genes on Bs, the latest research studies [25,44,56,75,77,78,79] have also found protein coding intact genes that we call “B essential genes” (see definitions in Box 1) which might be critical for the survival and transmission of Bs during their earlier stages of evolution (see details in next topic section). To create a reference of B-linked genes, we have organized a database that contain a list of genes detected in different species (Supplementary Dataset S1).…”
Section: Genome Composition Origin and Evolution Of Bsmentioning
confidence: 99%
“…The integrative Illumina and Pacbio sequencing data analysis of several cichlids species from Lake Malawi identified many gene fragments and genes located on Bs, some of which could possibly function in the regulation of Bs establishment [44]. The sequences of microdissected Bs in a fish species, Asian Seabass, were assembled and their annotations recorded a total of 75 genes out of which 10 genes, including ASTN2, BRE, DPF3, FBXO33, FKBP, GABRB2, MYT1L, RAB14, RXRAB, and PACRG, were known to be involved with particular expression in the brain and gonads [79].…”
Section: Discovering B Genes: the Current Arena For B-omicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their ability to adapt to varying salinities, euryhaline fishes provide an excellent model to understand the genetic basis of salt acclimation in the aquatic environment [ 30 , 31 , 32 , 33 ]. Asian seabass ( L. calcarifer ; Bloch, 1790), also known as barramundi or giant perch, is an euryhaline, carnivorous teleost, popular as a food fish in southeast Asia, Australia, and most of the Indian subcontinent [ 34 , 35 , 36 , 37 , 38 , 39 ]. Asian seabass is catadromous (fish that spend most of their life in freshwater, but spawn in seawater), although Asian seabass do not necessarily always migrate [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Milani et al Another interesting animal group for B studies is represented by fish species. Komissarov et al [4] investigate Bs of the Asian Seabass (Lates calcarifer), and give support to the view that Bs contribute to the variations in the genome among individuals and populations of the species. Among fish, cichlids have appeared as an interesting model for B studies.…”
mentioning
confidence: 89%